2011
DOI: 10.1111/j.1365-2745.2011.01821.x
|View full text |Cite
|
Sign up to set email alerts
|

Species- and community-level patterns in fine root traits along a 120 000-year soil chronosequence in temperate rain forest

Abstract: 1. Below-ground plant functional traits regulate plant-soil interactions and may therefore strongly influence ecosystem responses to global change. Despite this, knowledge of how fine-root functional traits vary among plant species and along environmental gradients has lagged far behind our understanding of above-ground traits. 2. We measured species-and community-level root and leaf trait responses for 50 temperate rain forest species from 28 families of ferns, woody and herbaceous angiosperms and conifers, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
291
4
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(326 citation statements)
references
References 50 publications
29
291
4
2
Order By: Relevance
“…On the one hand, following the resource economics hypothesis (Grime 1977;Craine 2009), poor soils select for species with thick fine-roots that live long, so that valuable plant resources are conserved (Eissenstat and Yanai 1997;Aerts and Chapin 2000;Wahl and Ryser 2000;Pérez-Ramos et al 2012;Reich 2014); such relationships between fine-root traits and the soil environment might also exist within species. A contrasting hypothesis, however, predicts thinner fine-roots on poor soils, because these roots grow fast and can more efficiently exploit the soil for resources (Eissenstat 1992;Ryser and Lambers 1995;Eissenstat and Yanai 1997;Ostonen et al 2007b;Holdaway et al 2011;Prieto et al 2015). Both hypotheses have been corroborated and refuted with empirical data (e.g.…”
Section: Introductionmentioning
confidence: 66%
“…On the one hand, following the resource economics hypothesis (Grime 1977;Craine 2009), poor soils select for species with thick fine-roots that live long, so that valuable plant resources are conserved (Eissenstat and Yanai 1997;Aerts and Chapin 2000;Wahl and Ryser 2000;Pérez-Ramos et al 2012;Reich 2014); such relationships between fine-root traits and the soil environment might also exist within species. A contrasting hypothesis, however, predicts thinner fine-roots on poor soils, because these roots grow fast and can more efficiently exploit the soil for resources (Eissenstat 1992;Ryser and Lambers 1995;Eissenstat and Yanai 1997;Ostonen et al 2007b;Holdaway et al 2011;Prieto et al 2015). Both hypotheses have been corroborated and refuted with empirical data (e.g.…”
Section: Introductionmentioning
confidence: 66%
“…Previous studies demonstrated that leaf N and P variation reflected environmental conditions more than plant intrinsic characteristics, such as genotype (Ågren and Weih 2012) and taxonomy (Zhang et al 2012). Although root nutrient concentrations were tightly associated with root diameter (Gordon and Jackson 2000), hierarchical branching and architecture (Iversen 2014;, they were also responsive indicators of soil nutrient availability Holdaway et al 2011) and climate at global and regional scale (Chen et al 2013;Yuan et al 2011). By contrast, stem which responsible for supporting and nutrient and water transport differed significantly in its construction costs among plant growth forms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, partitioning of P could become important for coexistence in retrogressive ecosystems where P is limiting [20]. However, no study has yet quantified the importance of these mechanisms in driving diversity patterns during long-term pedogenesis, although there is growing interest in shifts in the belowground traits of plants and plant functional diversity along soil chronosequences [27].…”
Section: Box 2 Pedogenic Changes Along Long-term Soil Chronosequencesmentioning
confidence: 99%